(untitled) (Quinto Sol, 2018)
This article analyzes the editorial position of the Peronist magazine Línea in the face of the formation of the Multipartidaria between 1981 and 1982, during the Argentine military dictatorship (1976-1983). The Multipartidaria brought together the main Argentine political parties and functioned as a tool to pressure the military government of the time to lay the foundations of the transition to democracy. However, it featured a more “moderate” sector, inclined to the agreement with the dictatorship, and a “harder” one, not inclined to agreement with the dictatorship. The paper studies how Línea evaluated the emergence of this new political space, what position it should adopt in the face of the dictatorship and how the Peronism that integrated it was to be handled.